Analisis Kendala Internal Mahasiswa dalam Menulis Karya Ilmiah - Rahmiati, Rahmiati (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2014)
This paper presents research on the analysis of internal hinderances students encounter in writing academic papers in higher education context. The aim is to canvass university student’s espoused conceptions of the internal hinderances and solutions regarding their difficulties in writing academic works. Data were generated from individual interviews and focus group discussions with 56 university learners. Data were analyzed using inductive and deductive approaches. The findings indicate several key findings related to what internal hinderaces students face in producing academic writing. Among the internal hinderances are issues related to laziness to write, lack of mood in writing, difficulties in findings topics or ideas to write, lack of self confidence in writing, and difficulties to start writing. This paper also reveals several strategic internal solutions to overcome those internal hinderance which include building internal motivation to write, changing thinking paradigm related to writing, and being creative in writing. Keywords: Writing, Academic Papers, Difficulties